The Use of Tourism Picture in Teaching Writing of Descriptive Texts in EFL Classroom - Hafizah, Reni (VELES Voices of English Language Education Society, 2019)
This research was intended to know the effectiveness of tourism picture in teaching writing of descriptive text for the tenth graders of MA NW Rempung in school year 2017-2018. The design of this research was a pre-experimental research with pre-test and post-test design. The result of the dat was analized by using SPSS 22 for windows programe.The sample was 26 students of the tenth graders (IPS-X) of MA NW Rempung in school year 2017-2018. The instrument was a subjective test in form of writing test. The result was analyzed by using descriptive statistics and a paired sample t-Test to proved whether the alternative hypothesis was accepted or not. The present researcher   found that the mean score of pre-test was 59.62 while the mean score of post-test was 75.15. In paired-sample t-test there was a significant difference in the mean scores between pre-test and the post-test, t (df=25) = 44.16 at p = .000, it means that the null hypothesis was rejected and alternative hypothesis was accepted. It implies that Tourism Picture was significantly effective in teaching writing of descriptive text for the tenth graders of MA NW Rempung in school year 2017-2018.